At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

3x-2y=-7
2x-5y=10 how to solve by elimination


Sagot :

Multiply 3x-2y=-7 by 2 which will end up looking like this: 6x-4y=-14.
then multiply 2x-5y=10 by -3 which will end up looking like this: -6x+15y=-30.
The set them like this 6x-4y=-14
                                 -6x+15y=-30
That will get rid of the x variable.  then add the equations which will get you to 11y=-44.  Then divided -44 by 11 which gives you -4. So y=-4.  Take -4 and put it back into the first equation (3x-2y=-7) for y.  Then solve for x. :)  Hope that helps!